Resonant inelastic X-ray scattering determination of the electronic structure of oxyhemoglobin and its model complex - Yan, James J.; Kroll, Thomas; Baker, Michael L.; Wilson, Samuel A.; Decréau, Richard; Lundberg, Marcus; Sokaras, Dimosthenis; Glatzel, Pieter; Hedman, Britt; Hodgson, Keith O.; Solomon, Edward I. (Proceedings of the National Academy of Sciences - PNAS, 2019)
Hemoglobin and myoglobin are oxygen-binding proteins with S = 0 heme FeO₂⁸ active sites. The electronic structure of these sites has been the subject of much debate. This study utilizes Fe K-edge X-ray absorption spectroscopy (XAS) and 1s2p resonant inelastic X-ray scattering (RIXS) to study oxyhemoglobin and a related heme FeO₂⁸ model compound, [(pfp)Fe(1-MeIm)(O₂)] (pfp = meso-tetra(α,α,α,α-o-pivalamido-phenyl)porphyrin, or TpivPP, 1-MeIm = 1-methylimidazole) (pfpO₂), which was previously analyzed using L-edge XAS. The K-edge XAS and RIXS data of pfpO₂ and oxyhemoglobin are compared with the data for low-spin FeII and FeIII [Fe(tpp)(Im)₂]0/+ (tpp = tetra-phenyl porphyrin) compounds, which serve as heme references. The X-ray data show that pfpO₂ is similar to FeII, while oxyhemoglobin is qualitatively similar to FeIII, but with significant quantitative differences. Density-functional theory (DFT) calculations show that the difference between pfpO₂ and oxyhemoglobin is due to a distal histidine H bond to O₂ and the less hydrophobic environment in the protein, which lead to more back-bonding into the O₂. A valence bond configuration interaction multiplet model is used to analyze the RIXS data and show that pfpO₂ is dominantly FeII with 6–8% FeIII character, while oxyhemoglobin has a very mixed wave function that has 50–77% FeIII character and a partially polarized Fe–O₂ π-bond.